2017
DOI: 10.1140/epjc/s10052-017-4737-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the internal structures of X(4140), X(4274), X(4500) and X(4700)

Abstract: We investigate the newly observed X (4500) and X (4700) based on the diquark-antidiquark configuration within the framework of QCD sum rules. Both of them may be interpreted as the D-wave cscs tetraquark states of J P = 0 + , but with opposite color structures, which is remarkably similar to the result obtained in Chen and Zhu (Phys Rev D 83:034010, 2011) that X (4140) and X (4274) can be both interpreted as the S-wave cscs tetraquark states of J P = 1 + , also with opposite color structures. However, the ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
285
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(300 citation statements)
references
References 60 publications
(104 reference statements)
7
285
1
7
Order By: Relevance
“…From the calculation with the QCD sum rule in Ref. [29], one may assign the X(4500) and X(4700) as the two D-wave cscs tetraquark states of J P = 0 + . In another analysis [30,31], the former state is assigned as the first radially excited state of the [ proposed that the X(4140) and the X(4274) belong to the ground state 1S-multiplet of diquark-antidiquark tetraquarks while the X(4500) and the X(4700) are radially excited 2S states.…”
Section: +219mentioning
confidence: 99%
“…From the calculation with the QCD sum rule in Ref. [29], one may assign the X(4500) and X(4700) as the two D-wave cscs tetraquark states of J P = 0 + . In another analysis [30,31], the former state is assigned as the first radially excited state of the [ proposed that the X(4140) and the X(4274) belong to the ground state 1S-multiplet of diquark-antidiquark tetraquarks while the X(4500) and the X(4700) are radially excited 2S states.…”
Section: +219mentioning
confidence: 99%
“…In Ref. [2], Chen et al study the newly observed X(4500) and X(4700) based on the diquarkantidiquark configuration within the framework of QCD sum rules, and interpret them as the D-wave cscs tetraquark states with J P = 0 + . In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be equally promising for gas sensing applications especially for reducing gases because the change in electrical resistance under different conditions. TiO 2 nanostructures have been synthesized by various techniques, including electron-beam evaporation [5], chemical coprecipitation [6], metal-organic decomposition (MOD) [7], plasma enhanced chemical vapor deposition (PECVD) [8] and solution-based methods [9]. Among these, sol-gel is one of the most successful methods, its simplicity and speed, the possibility of coating the both sides and forming multilayer and mixed layers under different preparation conditions, which allows controlling parameters of the nanostructures [10].…”
Section: Introductionmentioning
confidence: 99%